Reverse Patriarchy: The Concept of Matriarchy in The Artemyra Nation in The Comic by Shinobu Ohtaka's The Adventure of Sinbad - Sudarmadi, Vania Ardyna; Syihabuddin, Syihabuddin (Pusat Studi Gender Universitas Jember, 2024)
In the social order, there are usually known for two genders that play a role, they are men and women, along with their respective roles in society. In modern society, there are concepts of patriarchy and matriarchy. Patriarchy is a concept that lineage is determined by the paternal line and men have the right to be dominant while women are subordinate. Matriarchy is a concept regarding the prioritisation of women in society by placing women as determinants of lineage and upholding gender equality. The author conducts research related to these two concepts by focusing on understanding the concept of matriarchy in the Artemyra nation in Shinobu Ohtaka's The Adventure of Sinbad comic. The method used in this research is a descriptive method with a qualitative approach. The data source used is The Adventure of Sinbad comic chapters 46, 47, 51, 53, and 54. Based on the results of the analysis, it can be understood that the concept of matriarchy in Artemyra is not a real matriarchy but a reverse patriarchy. Reverse patriarchy, like the concept of patriarchy in general, places one gender in a dominant position. In Artemyra, it is women who dominate the society. Reverse patriarchy has little possibility of happening in modern society because the concept of matriarchy itself upholds gender equality.